Determination of the critical plane orientation depending on the fatigue curves for bending and torsion (Fracture and Structural Integrity, 2017)
This paper contains a proposition setting out a new way of determining an orientation angle of the critical plane. The applied method involves an analysis of fatigue life results’ scatter of several selected materials on the basis of a new criterion of multiaxial fatigue. The expression for the equivalent stress was derived on the basis of pure bending and pure torsion. The paper also contains a verification of the effectiveness of the proposed model by analyzing scatter bands and the value of the ratio of normal to shear stresses.
Keywords: Critical plane; Fatigue life; Equivalent stress; Scatter analysys